Uncovering a novel SERPING1 pathogenic variant: insights into the aggregation of C1-INH in hereditary angioedema - Lingxi Jiang; Chao Dai; Suyang Duan; Tingting Wang; Chunbao Xie; Luhan Zhang; Zimeng Ye; Xiumei Ma; Yi Shi (Orphanet Journal of Rare Diseases)
Abstract Background Hereditary angioedema (HAE) is a rare autosomal dominant genetic disease characterized by recurrent edema and a potentially fatal risk. Despite its severity, there is a notable lack of effective methods for predicting and preventing HAE attacks. This study aims to thoroughly investigate the underlying pathological mechanisms of HAE and identify potential biomarkers that could aid in its prediction and prevention. Results In our investigation, we have discovered a novel pathogenic variant of the SERPING1 gene, specifically c.708T > G, in a Han family affected by HAE. Our observations indicate that this variant leads to an increase in the accumulation of C1-INH within the endoplasmic reticulum (ER), resulting in the upregulation of GRP75 protein expression. This cascade of events resulted in Ca2+ overload, disruption of mitochondrial structure and function, and eventually triggered apoptosis. Using siRNA to knock down GRP75 mitigates cellular calcium overload and mitochondrial damage induced by the SERPING1 mutation. Conclusion Based on our findings, we propose that the detection of intracellular Ca2+ concentration could serve as a valuable biomarker for predicting acute attacks of HAE in patients. This discovery holds significant implications for the development of more targeted and effective strategies in the management of HAE.